Air filter filtration material, method for using air filter filtration material, and air treatment device
The air filter media utilizes a porous membrane with specific surface characteristics to inhibit mold growth, addressing the limitations of conventional air filter media in high humidity environments.
Patent Information
- Application Number
- JP2024169374
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-09-27
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Conventional air filter media often experience mold growth, which is not effectively addressed by existing antibacterial reinforcement materials.
The air filter media incorporates a porous membrane with an average surface height of 6 μm or more and a contact angle of water at 90 degrees or more, which suppresses mold growth without the need for antibacterial agents.
This configuration effectively prevents mold growth for an extended period, even in environments with high relative humidity, while maintaining high collection efficiency and low pressure loss.
Smart Images

Figure 2025060487000001_ABST
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE The present disclosure relates to air filter media, methods of using air filter media, and air treatment devices. [Background technology]
[0002] Conventionally, mold has sometimes grown on air filter media that capture dust and other particles contained in the air.
[0003] In response to this, for example, Patent Document 1 (JP Patent Publication No. 2003-205211) proposes an air filter medium in which an antibacterial reinforcing material made of inorganic, organic, or natural antibacterial agents is laminated to a polytetrafluoroethylene porous membrane. DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0004] For such air filter media, a new means for exerting antibacterial properties is desired. [Means for solving the problem]
[0005] The air filter medium according to a first aspect has a porous membrane having an average surface height Rc of 6 μm or more and a water contact angle of the membrane surface of 90 degrees or more.
[0006] The air filter medium is preferably an antifungal air filter medium.
[0007] This air filter medium is suppressed from growing mold.
[0008] An air filter medium according to a second aspect is the air filter medium according to the first aspect, wherein the average surface height Rc of the porous membrane is 36 μm or more.
[0009] The average surface height Rc of the porous membrane is preferably 37 μm or more, and more preferably 38 μm or more.
[0010] This air filter medium is more likely to inhibit the growth of mold for a longer period of time.
[0011] An air filter medium according to a third aspect is the air filter medium according to either the first or second aspect, in which the arithmetic mean roughness Ra of the surface of the porous membrane is 6 μm or more.
[0012] This air filter medium is likely to inhibit the growth of mold.
[0013] An air filter medium according to a fourth aspect is the air filter medium according to any one of the first aspect to the third aspect, in which the average pore size of the porous membrane is 2 μm or more.
[0014] This air filter medium is likely to inhibit the growth of mold.
[0015] An air filter medium according to a fifth aspect is the air filter medium according to any one of the first aspect to the fourth aspect, in which the average pore size of the porous membrane is 10 μm or less.
[0016] An air filter medium according to a sixth aspect is the antifungal air filter medium according to any one of the first aspect to the fifth aspect, in which the porous membrane has a thickness of 100 μm or more.
[0017] The thickness of the porous membrane is preferably 150 μm or more.
[0018] This air filter medium is likely to inhibit the growth of mold.
[0019] An air filter medium according to a seventh aspect is the air filter medium according to any one of the first aspect to the sixth aspect, in which the contact angle with an aqueous solution of isopropyl alcohol with a concentration of 30% by volume is 127 degrees or more.
[0020] This air filter medium is capable of suppressing the growth of mold for a long period of time.
[0021] An air filter medium according to an eighth aspect is the antifungal air filter medium according to any one of the first aspect to the seventh aspect, wherein the porous membrane contains a fluororesin.
[0022] This air filter medium has a porous film containing a fluororesin, which inhibits the growth of mold.
[0023] An air filter medium according to a ninth aspect is the air filter medium according to any one of the first aspect to the eighth aspect, in which the porous membrane does not contain an antifungal agent.
[0024] This air filter medium is capable of suppressing the growth of mold even if the porous membrane does not contain a mold inhibitor.
[0025] An air filter medium according to a tenth aspect is the air filter medium according to any one of the first aspect to the ninth aspect, and is used in an environment with a relative humidity of 60% or more.
[0026] This air filter medium is capable of suppressing the growth of mold even when used in an environment where mold is likely to grow.
[0027] A method for using an air filter medium according to an eleventh aspect comprises using the air filter medium according to any one of the first to ninth aspects in an environment with a relative humidity of 60% or more.
[0028] According to this method of using the air filter medium, the air filter medium can be used while suppressing the growth of mold even in an environment where mold is likely to grow.
[0029] An air treatment device according to a twelfth aspect includes the air filter medium according to any one of the first aspect to the tenth aspect.
[0030] This air treatment device makes it possible to treat air using an air filter medium. [Brief description of the drawings]
[0031] [Figure 1] FIG. 2 is a schematic cross-sectional view showing the layer structure of an antifungal air filter medium 30a. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing the layer structure of an antifungal air filter medium 30b. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing the layer structure of an antifungal air filter medium 30c. [Figure 4] FIG. 2 is a schematic cross-sectional view showing the layer structure of an antifungal air filter medium 30d. [Diagram 5] FIG. 2 is an external perspective view of the filter pack. [Figure 6] FIG. 2 is an external perspective view of the air filter unit. [Figure 7] FIG. 1 is a schematic diagram of an air treatment device. [Figure 8] 1 is a photograph showing the state of Example 1 and Comparative Example 1 three days after the start of a test conforming to the mold resistance test of JIS Z2911. [Figure 9] 1 is a photograph showing the state of Example 1 and Comparative Example 1 one week after the start of a test conforming to the mold resistance test of JIS Z2911. [Figure 10] 1 is a photograph showing the state of Example 1 and Example 3 after 4 weeks of culture in the ISO 846 test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] Hereinafter, an anti-fungal air filter material according to one embodiment of the air filter material, a method for using the anti-fungal air filter material according to one embodiment of the method for using the air filter material, and an air treatment device will be described using embodiments as examples.
[0033] (1) Anti-mold air filter media The antifungal air filter medium includes a porous membrane. The porous membrane has an average surface height Rc of 6 μm or more. The water contact angle of the porous membrane surface is 90 degrees or more. This antifungal air filter medium can suppress the generation of mold in the porous membrane.
[0034] The anti-mold air filter medium preferably has a particle collection efficiency of 95.0% or more, more preferably 99.5% or more, and even more preferably 99.95% or more, when air containing NaCl particles having a particle diameter of 0.1 μm is passed through the medium at a flow rate of 5.3 cm / sec.
[0035] The antifungal air filter medium preferably has a pressure loss of less than 250 Pa, more preferably less than 200 Pa, and may be 30 Pa or more and 190 Pa or less when air is passed through it at a flow rate of 5.3 cm / sec.
[0036] (2) Example of the composition of anti-mold air filter media The specific configuration of the above-mentioned antifungal air filter medium is not particularly limited.
[0037] For example, as shown in Fig. 1, the antifungal air filter medium 30a may be configured by stacking the breathable support material 21 and the porous membrane 31 in order in the air flow direction. Here, the porous membrane 31 may be disposed on the upstream side or downstream side of the breathable support material 21 in the air flow.
[0038] For example, like the mold-proofing air filter medium 30b shown in FIG. 2, an upstream-permeable support material 21a, a porous membrane 31, and a downstream-permeable support material 21b may be configured by overlapping them in the air flow direction.
[0039] Also, like the mold-proof air filter medium 30c shown in FIG. 3, the upstream-permeable support material 21a, the first porous membrane 31a, the second porous membrane 31b, and the downstream-permeable support material 21b may be stacked in order in the air flow direction.
[0040] Furthermore, as in the case of an antifungal air filter medium 30d shown in FIG. 4, an upstream breathable support material 21a, a first porous membrane 31a, an intermediate breathable support material 21c, a second porous membrane 31b, and a downstream breathable support material 21b may be configured by stacking them in order in the air flow direction.
[0041] In addition, a pre-collection layer, which is a membrane with smaller pressure loss and smaller collection efficiency, may be provided on the upstream side of the porous membrane 31 or the first porous membrane 31a.
[0042] The method of overlapping these films, materials, etc. is not particularly limited, and they may be laminated by utilizing the anchor effect caused by partial melting by heating or melting a hot melt resin, or by using a reactive adhesive, or they may simply be laminated.
[0043] (3) Porous membrane The porous membrane has an average surface height Rc of 6 μm or more, and a water contact angle of the membrane surface of 90 degrees or more. When the average surface height Rc of the porous membrane is 6 μm or more, it is easy to suppress the penetration of water into the porous membrane, which promotes the generation of mold, and it is easy to maintain the porous membrane in a dry state. In addition, since the water contact angle of the membrane surface of the porous membrane is 90 degrees or more, the water repellency of the porous membrane surface is good, water is easily repelled, and water is not easily retained on the surface of the porous membrane. As a result, the generation of mold in the porous membrane is suppressed. The present disclosure was made by first finding that there is a correlation between the tendency of mold to occur in a porous membrane having a water contact angle of 90 degrees or more on the membrane surface and the average surface height Rc of the porous membrane.
[0044] In addition, the average height Rc of the surface of the porous membrane is preferably 36 μm or more, more preferably 37 μm or more, even more preferably 38 μm or more, even more preferably 40 μm or more, and most preferably 100 μm or more, from the viewpoint of suppressing mold growth for a longer period of time.
[0045] The average surface height Rc of the porous membrane is not particularly limited, but is preferably, for example, 300 μm or less, and more preferably 200 μm or less.
[0046] The average surface height Rc is a value measured in accordance with the method described in JIS B 0601 (2013).
[0047] In addition, the average height Rc of the surface of the porous film can be reduced by reducing the amount of liquid lubricant used in the manufacturing process (added when the powder obtained by coagulation is extruded using a paste extrusion device to obtain a sheet-shaped molded body) in the case of a fluororesin porous film, and can be increased by increasing the amount of liquid lubricant. In addition, the average height Rc of the porous film obtained can be adjusted by adjusting the types and compounding ratios of the components mixed when obtaining the fluororesin porous film. Furthermore, in the case of a fluororesin porous film, the average height Rc of the surface of the porous film can be increased by reducing the stretch ratio when stretching the unsintered fluororesin film, and can be reduced by increasing the stretch ratio.
[0048] The water contact angle of the porous membrane is 90 degrees or more, preferably 120 degrees or more, and more preferably 140 degrees or more, from the viewpoint of making it difficult for water to be retained on the surface of the porous membrane and making it easy to reduce the contact area with the porous membrane.
[0049] The contact angle of water is determined by the θ / 2 method and is measured 30 seconds after a droplet is dropped onto the surface of the porous membrane.
[0050] The contact angle of a 20% by volume aqueous solution of isopropyl alcohol is preferably 127 degrees or more, and more preferably 130 degrees or more, from the viewpoint that water is less likely to be retained on the surface of the porous membrane and the contact area with the porous membrane is easily reduced.
[0051] The contact angle of the 20% by volume aqueous solution of isopropyl alcohol refers to the contact angle obtained by the θ / 2 method. The contact angle of the 20% by volume aqueous solution of isopropyl alcohol is the contact angle of the droplet measured 30 seconds after the droplet is dropped onto the surface of the porous membrane. The 20% by volume aqueous solution of isopropyl alcohol has a volume ratio of water:IPA of 80:20.
[0052] The contact angle of a 30% by volume aqueous solution of isopropyl alcohol is preferably 127 degrees or more, and more preferably 129 degrees or more, from the viewpoint that water is less likely to be retained on the surface of the porous membrane and the contact area with the porous membrane is easily reduced.
[0053] The contact angle of the 30% by volume aqueous solution of isopropyl alcohol refers to the contact angle obtained by the θ / 2 method. The contact angle of the 30% by volume aqueous solution of isopropyl alcohol is the contact angle of the droplet measured 30 seconds after the droplet is dropped onto the surface of the porous membrane. The 30% by volume aqueous solution of isopropyl alcohol has a volume ratio of water:IPA of 70:30.
[0054] In addition, the surface tension of the aqueous solution containing isopropyl alcohol is lower than that of the water contact angle test, so it can be said to be a liquid that is more easily absorbed than water. Therefore, the contact angle of the aqueous solution containing isopropyl alcohol tends to be smaller than that of the water contact angle test.
[0055] The arithmetic mean roughness Ra of the surface of the porous membrane is preferably 6 μm or more, more preferably 7 μm or more, and even more preferably 20 μm or more, from the viewpoint of suppressing the generation of mold for a longer period of time. The arithmetic mean roughness Ra of the surface of the porous membrane is not particularly limited, but is, for example, 100 μm or less. The arithmetic mean roughness Ra of the surface is a value measured in accordance with the method described in JIS B 0601 (2013).
[0056] In addition, the arithmetic mean roughness Ra of the surface of the porous membrane can be adjusted by the amount of liquid lubricant used in the manufacturing process, for example, in the case of a fluororesin porous membrane. In addition, the arithmetic mean roughness Ra of the obtained porous membrane can also be adjusted by adjusting the type and compounding ratio of the components mixed when obtaining the fluororesin porous membrane.
[0057] The average pore size of the porous membrane is preferably 2 μm or more, more preferably 2.2 μm or more, from the viewpoint that water is less likely to be retained in the porous membrane. The average pore size of the porous membrane may be, for example, 10 μm or less. This average pore size is also called the average flow path size, and is measured in accordance with ASTM F316-86.
[0058] The thickness of the porous membrane is, for example, preferably 100 μm or more, more preferably 130 μm or more, and even more preferably 150 μm or more. The thicker the porous membrane, the larger the pore size, making it difficult for water to be retained, while increasing the collection efficiency. In addition, the thickness of the porous membrane refers to the total thickness when multiple porous membranes are laminated. Here, when two or more porous membranes are laminated, it is preferable that the porous membrane located on the upstream side of the air flow to pass through has a larger thickness and a larger pore size than the porous membrane located on the downstream side of the air flow. This makes it easier to suppress the occurrence of mold on the upstream side of the porous membrane. In addition, the thickness of the porous membrane can be increased by increasing the amount of liquid lubricant used in the manufacturing process, for example, in the case of a fluororesin porous membrane, and can be increased by decreasing the stretching ratio.
[0059] The above-mentioned porous membrane can suppress the generation of mold even if it does not contain antifungal agent in the porous membrane.If it contains antifungal agent, it may fall off from the porous membrane and deteriorate the performance as air filter material, so it is preferable that the porous membrane does not contain antifungal agent such as antibacterial agent.In addition, the antifungal agent is not particularly limited, and can be, for example, organic antifungal agent such as benzimidazole compound, pyrithione compound, isothiazolin compound, etc., or inorganic antifungal agent containing photocatalyst containing transition metal element.
[0060] In addition, the pressure loss of the porous membrane when air is passed through it at a flow rate of 5.3 cm / sec is preferably less than 250 Pa, more preferably less than 200 Pa, and may be 30 Pa or more and 190 Pa or less. For example, in the case of a fluororesin porous membrane, the pressure loss of the porous membrane can be suppressed by increasing the amount of liquid lubricant used in the manufacturing process, by increasing the stretch ratio, and by increasing the calender temperature.
[0061] (4) Porous membrane containing fluororesin The porous membrane is preferably a fluororesin porous membrane, which is a porous membrane containing a fluororesin. More specifically, the porous membrane is preferably mainly composed of a fluororesin and has a porous membrane structure having fibrils (fibers) not shown and nodes (nodes) connected to the fibrils. Here, "mainly" means that when multiple types of components are contained, the fluororesin is contained in the largest amount.
[0062] An example of the component different from the fluororesin is an inorganic filler which is a non-melt processable component (component B) that does not become fibrous, as described below.
[0063] The fluororesin used in the fluororesin porous membrane may be composed of one kind of component, or may be composed of two or more kinds of components. In addition, as the fluororesin composed of two or more kinds of components, for example, a mixture of three components, namely, fibrous PTFE (hereinafter also referred to as component A), non-fibrous non-thermal melt processable component (hereinafter also referred to as component B), and non-fibrous heat melt processable component (hereinafter also referred to as component C) with a melting point of less than 320°C, is exemplified. The fluororesin porous membrane is preferably composed of a combination of these three kinds of components. Compared with a fibrous PTFE (high molecular weight PTFE) porous membrane, the fluororesin porous membrane composed of these three kinds of components has a membrane structure with many voids and a thick membrane thickness, so that fine particles in the gas can be collected in a wide area in the thickness direction of the filter medium, thereby improving the dust holding capacity. By forming the porous membrane from these three kinds of components, it is possible to particularly increase the dust holding capacity of liquid particles rather than solid particles.
[0064] The above three components will now be described in more detail.
[0065] (4-1) Component A: PTFE that can be fibrillated The fibrous PTFE is, for example, a high molecular weight PTFE obtained by emulsion polymerization or suspension polymerization of tetrafluoroethylene (TFE). The term "high molecular weight" as used herein means that the PTFE is easily fibrous during stretching in the production of a porous membrane, and that fibrils with long fiber length can be obtained, and has a standard specific gravity (SSG) of 2.130 to 2.230, and has a molecular weight of a size that does not melt flow due to high melt viscosity. The SSG of the fibrous PTFE is preferably 2.130 to 2.190, more preferably 2.140 to 2.170, from the viewpoint of being easily fibrous and being able to obtain fibrils with long fiber length. If the SSG is too high, the stretchability of the mixture of the components A to C may be deteriorated, and if the SSG is too low, the rollability may be deteriorated, the homogeneity of the porous membrane may be deteriorated, and the pressure loss of the porous membrane may be increased. In addition, from the viewpoint of being easily fibrous and being able to obtain fibrils with long fiber length, PTFE obtained by emulsion polymerization is preferable. Standard specific gravity (SSG) is measured in accordance with ASTM D 4895.
[0066] The presence or absence of fibrotic property, that is, whether or not it can be fibrotic, can be judged by whether or not paste extrusion, which is a typical method for molding high molecular weight PTFE powder made from TFE polymer, is possible. Usually, paste extrusion is possible because high molecular weight PTFE has fibrotic property. If the unsintered molded body obtained by paste extrusion has no substantial strength or elongation, for example, if the elongation is 0% and it breaks when pulled, it can be considered that it has no fibrotic property.
[0067] The high molecular weight PTFE may be modified polytetrafluoroethylene (hereinafter referred to as modified PTFE), may be homopolytetrafluoroethylene (hereinafter referred to as homo-PTFE), or may be a mixture of modified PTFE and homo-PTFE. The homo-PTFE is not particularly limited, and homo-PTFE disclosed in JP-A-53-60979, JP-A-57-135, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345 pamphlet, WO 2007 / 119829 pamphlet, WO 2009 / 001894 pamphlet, WO 2010 / 113950 pamphlet, WO 2013 / 027850 pamphlet, etc. can be suitably used. Among these, homo-PTFE having high stretchability and disclosed in JP-A-57-135, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345, WO 2007 / 119829, WO 2010 / 113950 and the like is preferred.
[0068] The modified PTFE is composed of TFE and a monomer other than TFE (hereinafter referred to as a modified monomer). The modified PTFE includes, but is not limited to, those uniformly modified by the modified monomer, those modified at the beginning of the polymerization reaction, and those modified at the end of the polymerization reaction. The modified PTFE may be, for example, those disclosed in JP-A-60-42446, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-64-1711, JP-A-2-261810, JP-A-11-240917, JP-A-11-240918, WO 2003 / 033555 pamphlet, WO 2005 / 061567 pamphlet, WO 2007 / 005361 pamphlet, WO 2011 / 055824 pamphlet, WO 2013 / 027850 pamphlet, etc., which can be suitably used. Among these, modified PTFEs having high stretchability and disclosed in JP-A-61-16907, JP-A-62-104816, JP-A-64-1711, JP-A-11-240917, WO 2003 / 033555, WO 2005 / 061567, WO 2007 / 005361, WO 2011 / 055824 and the like are preferred.
[0069] The modified PTFE contains TFE units based on TFE and modified monomer units based on modified monomers. The modified monomer units are a part of the molecular structure of the modified PTFE and are derived from the modified monomer. The modified PTFE contains the modified monomer units in an amount of preferably 0.001 to 0.500% by weight, more preferably 0.01 to 0.30% by weight, of the total monomer units. The total monomer units are the parts derived from all monomers in the molecular structure of the modified PTFE.
[0070] The modifying monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene (HFP), chlorofluoroolefins such as chlorotrifluoroethylene (CTFE), hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride (VDF), perfluorovinyl ethers, perfluoroalkylethylenes (PFAE), ethylene, etc. The modifying monomer used may be one type or multiple types.
[0071] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorounsaturated compounds represented by the following general formula (1). CF2 = CF-ORf (1) In the formula, Rf represents a perfluoro organic group.
[0072] In this specification, a perfluoro organic group is an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.
[0073] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) (PAVE) in which Rf in the above general formula (1) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5. Examples of the perfluoroalkyl group in PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group. Preferred examples of PAVE include perfluoropropyl vinyl ether (PPVE) and perfluoromethyl vinyl ether (PMVE).
[0074] The perfluoroalkylethylene (PFAE) is not particularly limited, and examples thereof include perfluorobutylethylene (PFBE), perfluorohexylethylene (PFHE), and the like.
[0075] The modifying monomer in the modified PTFE is preferably at least one selected from the group consisting of HFP, CTFE, VDF, PAVE, PFAE and ethylene.
[0076] Homo-PTFE is preferably contained in an amount of more than 50% by weight of the fibrous PTFE, in particular from the viewpoint of being easily fiberized and obtaining fibrils with long fiber length.
[0077] The PTFE that can be fiberized may be a combination of a plurality of the above-mentioned components.
[0078] From the viewpoint of maintaining the fibrous structure of the porous membrane, the content of the fibrillizable PTFE in the porous membrane is preferably more than 50% by weight.
[0079] (4-2) B component: A non-thermal melt processable component that does not become fibrous The non-fibrillating non-thermal melt processable component is unevenly distributed as non-fibrous particles mainly in the nodes, and acts to inhibit fibrillating PTFE from becoming fibrous.
[0080] Examples of non-fibrillating non-thermal melt processable components include components having thermoplastic properties such as low molecular weight PTFE, thermosetting resins, inorganic fillers, and mixtures thereof.
[0081] It is preferable that the thermoplastic component has a melting point of 320°C or higher and a high melt viscosity. For example, low molecular weight PTFE has a high melt viscosity, so it can remain in the nodes even when processed at a temperature above its melting point. In this specification, low molecular weight PTFE refers to PTFE having a number average molecular weight of 600,000 or less, a melting point of 320°C to 335°C, and a melt viscosity at 380°C of 100 Pa s to 7.0 x 10 5 It is PTFE with a hardness of Pa·s (see JP-A-10-147617).
[0082] Examples of the method for producing low molecular weight PTFE include a method in which a high molecular weight PTFE powder (molding powder) obtained by suspension polymerization of TFE or a high molecular weight PTFE powder (fine powder) obtained by emulsion polymerization of TFE is contacted with a specific fluoride at high temperature to cause thermal decomposition (see JP 61-162503 A), a method in which the high molecular weight PTFE powder or a molded body is irradiated with ionizing radiation (see JP 48-78252 A), and a method in which TFE is directly polymerized together with a chain transfer agent (see WO 2004 / 050727, WO 2009 / 020187, WO 2010 / 114033, etc.). The low molecular weight PTFE may be homo-PTFE, as with PTFE that can be fibrous, or may be modified PTFE containing the above-mentioned modified monomer.
[0083] Low molecular weight PTFE is not fibrotic. The presence or absence of fibrotic property can be judged by the above-mentioned method. Low molecular weight PTFE has no substantial strength or elongation in the unsintered molded body obtained by paste extrusion, for example, the elongation is 0%, and it breaks when pulled.
[0084] The low molecular weight PTFE is not particularly limited, but the melt viscosity at 380°C is preferably 1000 Pa·s or more, more preferably 5000 Pa·s or more, and even more preferably 10000 Pa·s or more. In this way, when the melt viscosity is high, even if the component C that is not fibrous and can be heat-melted is melted during the production of the porous membrane, the non-thermal melt-processable component that is not fibrous can remain in the nodule, and fibrous formation can be suppressed.
[0085] Thermosetting resins include, for example, epoxy, silicone, polyester, polyurethane, polyimide, phenol, and mixtures thereof. From the viewpoint of the workability of the coagulation described later, it is desirable to use thermosetting resins that are uncured and dispersed in water. All of these thermosetting resins can be obtained commercially.
[0086] Examples of inorganic fillers include talc, mica, calcium silicate, glass fiber, calcium carbonate, magnesium carbonate, carbon fiber, barium sulfate, calcium sulfate, and mixtures thereof. Among them, talc is preferably used from the viewpoint of affinity with high molecular weight PTFE that can be fiberized and specific gravity. Inorganic fillers having a particle diameter of 3 μm or more and 20 μm or less are preferably used from the viewpoint of forming a stable dispersion during the production of a porous membrane. The particle diameter is the average particle diameter and is measured by a laser diffraction / scattering method. All of these inorganic fillers are also available as commercially available products.
[0087] In addition, the non-melt-processable component that does not cause fiber formation may be a combination of a plurality of the above-mentioned components.
[0088] The non-fibrillating non-thermal melt processable component is preferably contained in the porous membrane in an amount of 1% by weight or more and 50% by weight or less. The non-fibrillating non-thermal melt processable component is preferably contained in an amount of 50% by weight or less, and the fibrous structure of the porous membrane is easily maintained. The non-fibrillating non-thermal melt processable component is preferably contained in an amount of 20% by weight or more and 40% by weight or less, and more preferably contained in an amount of 30% by weight ... more effectively prevented from being fibrous by being contained in an amount of 20% by weight or more and 40% by weight or less.
[0089] (4-3) C component: A component that can be processed by hot melting and does not become fibrous due to its melting point of less than 320°C. The non-fibrous hot melt processable component with melting point less than 320℃ (hereinafter also referred to as non-fibrous hot melt processable component) has fluidity when melted, and can melt and solidify at the node during the manufacture (stretching) of porous membrane, and can increase the strength of the entire porous membrane, and can suppress the deterioration of filter performance even if it is compressed in the later process.
[0090] The non-fibrous heat-melt processable component preferably has a melt viscosity of less than 10,000 Pa·s at 380°C. The melting point of the non-fibrous heat-melt processable component is the peak top of the heat of fusion curve obtained by heating the component to the melting point or higher at a heating rate of 10°C / min using a differential scanning calorimeter (DSC), melting it completely once, cooling it to the melting point or lower at a heating rate of 10°C / min, and then heating it again at a heating rate of 10°C / min.
[0091] The non-fibrous heat-meltable component includes heat-meltable fluoropolymers, polystyrene, polyethylene terephthalate (PET), polyester, polyamide, and other resins, or mixtures thereof, which can fully exhibit melting and fluidity at the stretching temperature during porous membrane production. Among them, heat-meltable fluoropolymers are preferred because of their excellent heat resistance and chemical resistance at the stretching temperature during porous membrane production. Heat-meltable fluoropolymers are represented by the following general formula (2): RCF = CR2 (2) (wherein R is independently selected from H, F, Cl, alkyl having 1 to 8 carbon atoms, aryl having 6 to 8 carbon atoms, cyclic alkyl having 3 to 10 carbon atoms, and perfluoroalkyl having 1 to 8 carbon atoms. In this case, all R may be the same, or any two R may be the same and the remaining R may be different from these, or all R may be different from each other.)
[0092] Useful examples of the compound represented by general formula (2) include, but are not limited to, perfluoroolefins such as fluoroethylene, VDF, trifluoroethylene, TFE, and HFP, chlorofluoroolefins such as CTFE and dichlorodifluoroethylene, (perfluoroalkyl)ethylenes such as PFBE and PFHE, perfluoro-1,3-dioxole, and mixtures thereof.
[0093] The fluoropolymer comprises at least one monomer represented by the above general formula (2), The above general formula (1) and / or the following general formula (3) R2C = CR2 (3) (wherein R are each independently selected from H, Cl, an alkyl group having 1 to 8 carbon atoms, an aryl group having 6 to 8 carbon atoms, and a cyclic alkyl group having 3 to 10 carbon atoms. In this case, all of the R may be the same, or any two or more of the R may be the same and these two or more R may be different from the remaining R, or all of the R may be different from each other. When there are a plurality of the other R, they may be different from each other.)
[0094] Useful examples of the compound represented by the general formula (1) include perfluoro(alkyl vinyl ether) (PAVE), preferably perfluoropropyl vinyl ether (PPVE) or perfluoromethyl vinyl ether (PMVE).
[0095] Useful examples of the compound represented by the general formula (3) include ethylene, propylene, and the like.
[0096] More specific examples of fluoropolymers include polyfluoroethylene derived from the polymerization of fluoroethylene, polyvinylidene fluoride (PVDF) derived from the polymerization of vinylidene fluoride (VDF), polychlorotrifluoroethylene (PCTFE) derived from the polymerization of chlorotrifluoroethylene (CTFE), fluoropolymers derived from the copolymerization of two or more different monomers represented by the above general formula (2), and fluoropolymers derived from the copolymerization of at least one monomer represented by the above general formula (2) and at least one monomer represented by the above general formula (1) and / or at least one monomer represented by the above general formula (3).
[0097] Examples of such polymers are those having copolymer units derived from VDF and hexafluoropropylene (HFP), TFE and at least one copolymerizable comonomer other than TFE (at least 3% by weight). The latter type of fluoropolymers include TFE / PAVE copolymers (PFA), TFE / PAVE / CTFE copolymers, TFE / HFP copolymers (FEP), TFE / ethylene copolymers (ETFE), TFE / HFP / ethylene copolymers (EFEP), TFE / VDF copolymers, TFE / VDF / HFP copolymers, TFE / VDF / CTFE copolymers, etc., or mixtures thereof.
[0098] In addition, the non-fibrous hot melt processable component may be a combination of a plurality of the above-mentioned components.
[0099] The content of the non-fibrotic heat melt processable component in the porous film is preferably 0.1% by weight or more and less than 20% by weight. By being less than 20% by weight, the non-fibrotic heat melt processable component is dispersed in the parts other than the nodes in the porous film, and the pressure loss of the porous film is suppressed from increasing. In addition, by being less than 20% by weight, it is easy to perform stretching at a high ratio of 40 times or more of elongation area ratio described later. By being 0.1% by weight or more of the non-fibrotic heat melt processable component in the porous film, it is easy to sufficiently suppress the deterioration of the filter performance of the porous film even if a compressive force or the like is applied in a later process. The content of the non-fibrotic heat melt processable component in the porous film is preferably 15% by weight or less, more preferably 10% by weight or less. In addition, the content of the non-fibrotic heat melt processable component in the porous film is preferably 0.5% by weight or more from the viewpoint of ensuring the strength of the porous film. Among them, it is particularly preferable that it is about 5% by weight.
[0100] The content of the non-fibrillating heat melt processable component is preferably 10% by weight or less in order to perform good stretching at an elongation area magnification of 40 times or more and 800 times or less.
[0101] In the porous membrane made of the three kinds of components described above, fibrils are mainly made of component A, and nodes are made of components A to C. Such nodes are formed relatively large in the porous membrane, and thus a thick porous membrane is formed. In addition, such nodes are relatively hard by containing a component that can be processed by heat melting and does not become fibrous, and play a role like a pillar that supports the porous membrane in the thickness direction, so that it is possible to suppress the deterioration of the filter performance of the porous membrane even if it is subjected to a compressive force in the thickness direction in the post-process such as lamination of the breathable support material or pleating processing described later.
[0102] (4-4) Other properties of porous membranes The fluororesin porous membrane preferably has a fiber diameter (average fiber diameter) of 50 nm to 250 nm, more preferably 60 nm to 200 nm. In addition, the first fluororesin porous membrane, which is disposed upstream of the second fluororesin porous membrane in the airflow, preferably has a larger fiber diameter.
[0103] The above-mentioned fluororesin porous membrane is not particularly limited, but may be produced by referring to the production method described in JP-A-2017-159281, for example.
[0104] (5) Breathable support material Even if the porous membrane is difficult to stand on its own due to its thin thickness, the breathable supporting material supports the porous membrane, thereby making it possible for the porous membrane to stand upright.
[0105] The material and structure of the breathable support material are not particularly limited, and examples thereof include nonwoven fabric, woven fabric, metal mesh, and resin net. Among them, nonwoven fabric having heat fusion properties is preferable in terms of strength, collection ability, flexibility, and workability. As for the nonwoven fabric, a nonwoven fabric in which some or all of the constituent fibers have a core / sheath structure, a two-layer nonwoven fabric consisting of a layer of fiber made of a low melting point material and a layer of fiber made of a high melting point material, and a nonwoven fabric having a heat fusion resin applied to the surface are preferable. Examples of such nonwoven fabrics include spunbond nonwoven fabrics. In addition, it is preferable that the core component has a higher melting point than the sheath component in the core / sheath structure nonwoven fabric. For example, examples of the combination of each material of the core / sheath include PET / PE, and high melting point polyester / low melting point polyester. Examples of the combination of low melting point material / high melting point material of the two-layer nonwoven fabric include PE / PET, PP / PET, PBT / PET, and low melting point PET / high melting point PET. Examples of nonwoven fabrics having a surface coated with a heat-fusible resin include PET nonwoven fabrics coated with EVA (ethylene vinyl acetate copolymer resin) and PET nonwoven fabrics coated with an olefin resin.
[0106] The material of the nonwoven fabric is not particularly limited, and may be polyolefin (PE, PP, etc.), polyamide, polyester (PET, etc.), aromatic polyamide, or a composite material of these.
[0107] The breathable support material can be bonded to the porous membrane by melting a portion of the breathable support material by heating, or by melting a hot melt resin, utilizing the anchor effect, or by using adhesion such as a reactive adhesive.
[0108] Compared with the above-mentioned porous membrane, the breathable support material has extremely low pressure loss, collection efficiency and dust capacity, and the pressure loss and collection efficiency may be 5% or less of those of the porous membrane, and may be essentially zero.
[0109] The pressure loss of the breathable support material is, for example, preferably 10 Pa or less, and more preferably 5 Pa or less. The collection efficiency of the breathable support material for NaCl having a particle diameter of 0.1 μm may be, for example, substantially 0 or approximately 0.
[0110] The thickness of the breathable support material is, for example, preferably 0.3 mm or less, and more preferably 0.25 mm or less.
[0111] The weight of the breathable support material is, for example, 20 g / m 2 More than 50g / m 2 It is preferable that:
[0112] The above-mentioned breathable support materials have very large openings and poor water retention, so that the antifungal performance of the antifungal air filter medium substantially depends on the antifungal properties of the porous membrane.
[0113] (6) Pre-collection material The antifungal air filter medium may include a pre-collection material that is arranged upstream of the porous membrane and that collects a portion of dust in the airflow.
[0114] From the viewpoint of keeping the pressure loss of the entire anti-mold air filter medium low, the pre-collection material preferably has a pressure loss of 5 Pa or more and less than 55 Pa, and more preferably 15 Pa or more and less than 45 Pa, when air is passed through it at a flow rate of 5.3 cm / sec.
[0115] Furthermore, the pre-trapping material preferably has a trapping efficiency for NaCl having a particle diameter of 0.3 μm of 15% or more and less than 85%, and more preferably 30% or more and less than 75%.
[0116] From the viewpoint of facilitating the folding operation when folding the air filter medium into pleats, the pre-collection material preferably has a thickness of 0.8 mm or less, more preferably 0.7 mm or less, and may be less than 0.4 mm. The thickness of the pre-collection material is not particularly limited, but may be, for example, 0.1 mm or more.
[0117] The average fiber diameter of the pre-collection material is preferably 0.8 μm or more and less than 2.0 μm.
[0118] The basis weight of the pre-collection material is not particularly limited, but is, for example, 10 g / m 2 More than 70g / m 2 and 30 g / m 2 More than 67g / m 2 It is preferable that:
[0119] Such a pre-collection material is not particularly limited, but may be made of a glass fiber filter material, or may be a nonwoven fabric or a fiber layer structure made of a fiber material manufactured by one of the melt-blown method, the electrospinning method, the sea-island method, and a hybrid method thereof. Hybrid methods include, for example, the melt-spinning method and the electret-blown method. The sea-island method is a method in which, for example, when fibers are formed by discharging from a plurality of discharge ports, the raw materials are made different depending on the discharge path, and the sea part is formed by some raw materials and the island part is formed by other different raw materials, so that the cross section has a sea-island structure. Here, a two-component or multiple-component polymer of the sea-island can be spun, and the sea component can be dissolved in a post-processing to leave the island part and make it into a fiber. It is possible to adjust the bulk density, stretchability, etc. by combining the raw materials by the discharge path. In the melt-blown method, a molten polymer is discharged from a nozzle by an extruder, and heated air is blown along the nozzle to form a thread. Here, by adjusting the amount of polymer discharged from the nozzle per unit time and the blowing speed of the heated air, etc., it is possible to obtain threads with a smaller diameter. In addition, the physical properties of the threads can also be changed by the melt viscosity of the polymer used. Examples of materials for producing the pre-collection material by the melt blown method, electrospinning method, sea-island method, or one of their hybrid methods include polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyamide (PA), polyacrylonitrile (PAN), polyvinylidene fluoride (PVdF), polyvinyl alcohol (PVA), polyurethane (PU), and mixtures thereof.
[0120] (7) Examples of uses Antifungal air filter media are used, for example, for the following purposes:
[0121] ULPA filters (Ultra low Penetration Air Filters) (for semiconductor manufacturing), HEPA filters (for hospitals and semiconductor manufacturing), cylindrical cartridge filters (for industrial use), bag filters (for industrial use), heat-resistant bag filters (for exhaust gas treatment), heat-resistant pleated filters (for exhaust gas treatment), SINBRAN (registered trademark) filters (for industrial use), catalytic filters (for exhaust gas treatment), filters with adsorbent (for HDD installation), vent filters with adsorbent (for HDD installation), vent filters (for HDD installation, etc.), vacuum cleaner filters (for vacuum cleaners), general-purpose multi-layer felt materials, cartridge filters for gas turbines (for gas turbine compatible products), cooling filters (for electronic equipment housings), etc. Freeze-drying materials such as freeze-drying containers, automotive ventilation materials for electronic circuits and lamps, container applications such as container caps, protective ventilation applications such as for electronic devices, ventilation / internal pressure regulation applications such as medical ventilation applications; Liquid filtration field including semiconductor liquid filtration filters (for semiconductor manufacturing), hydrophilic filters (for semiconductor manufacturing), chemical filters (for chemical liquid treatment), pure water production line filters (for pure water production), backwash type liquid filtration filters (for industrial wastewater treatment).
[0122] The antifungal air filter medium is preferably used in any one of food factories, pharmaceutical factories, clean rooms, and air purifiers.
[0123] The antifungal air filter medium is more likely to exert its effect when used in an environment where mold growth is particularly a concern. For example, the antifungal air filter medium is preferably used in an environment with a relative humidity of 60% or more, more preferably in an environment with a temperature of 20°C or more and a relative humidity of 60% or more, and even more preferably in an environment with a temperature of 25°C or more and a relative humidity of 70% or more.
[0124] (8) Filter pack Next, the filter pack will be described with reference to FIG.
[0125] FIG. 5 is a perspective view of the appearance of the filter pack 20. As shown in FIG.
[0126] The filter pack 20 includes the above-described antifungal air filter material (for example, antifungal air filter materials 30a to 30d, etc.). The antifungal air filter material of the filter pack 20 is a processed filter material that has been processed (pleated) into a zigzag shape in which mountain folds and valley folds are alternately repeated. The pleating can be performed, for example, by a rotary folding machine. The folding width of the filter material is not particularly limited, but is, for example, 25 mm or more and 280 mm or less. Since the filter pack 20 is pleated, the folding area of the filter material can be increased when the filter pack 20 is used in an air filter unit, and thus an air filter unit with high collection efficiency can be obtained.
[0127] In addition to the antifungal air filter medium, the filter pack 20 may further include a spacer (not shown) for maintaining the pleat spacing when used in an air filter unit. The material of the spacer is not particularly limited, but a hot melt resin is preferably used.
[0128] (9) Air filter unit Next, the air filter unit 1 will be described with reference to FIG.
[0129] FIG. 6 is a perspective view of the appearance of the air filter unit 1. As shown in FIG.
[0130] The air filter unit 1 includes the above-described antifungal air filter material or filter pack, and a frame 25 that holds the antifungal air filter material or filter pack. In other words, the air filter unit may be produced so that the antifungal air filter material that is not folded in a peak or valley shape is held in the frame, or the filter pack 20 is held in the frame 25. The air filter unit 1 shown in FIG. 6 is produced using the filter pack 20 and the frame 25.
[0131] Frame 25 is made, for example, by combining plate materials or by molding resin, and the gap between filter pack 20 and frame 25 is preferably sealed with a sealant. The sealant is for preventing leakage between filter pack 20 and frame 25, and is made of, for example, epoxy, acrylic, urethane, or other resin.
[0132] The air filter unit 1, which is equipped with a filter pack 20 and a frame body 25, may be a mini-pleat type air filter unit in which one filter pack 20 extending in a flat plate shape is held inside the frame body 25, or may be a V-bank type air filter unit or a single-header type air filter unit in which a plurality of filter packs extending in a flat plate shape are arranged side by side and held in a frame body.
[0133] (10) Air treatment equipment Next, the air treatment device 100 will be described with reference to FIG.
[0134] FIG. 7 is a perspective view of the exterior of the air treatment device 100. As shown in FIG.
[0135] The air treatment device 100 includes the above-described antifungal air filter medium (for example, antifungal air filter mediums 30a to 30d), a casing 50, a heat exchanger 51, a humidity adjustment unit 52, and a fan 53.
[0136] The casing 50 has an intake port 50a and an exhaust port 50b, and accommodates therein the antifungal air filter media 30a-30d, a heat exchanger 51, a humidity adjustment section 52, and a fan 53. The antifungal air filter media 30a-30d, the heat exchanger 51, the humidity adjustment section 52, and the fan 53 are arranged in this order from the intake port 50a toward the exhaust port 50b.
[0137] The heat exchanger 51 constitutes a part of a refrigerant circuit (not shown), and a refrigerant flows inside the heat exchanger 51. The air that has passed through the antifungal air filter materials 30a to 30d is heated or cooled when passing through the heat exchanger 51.
[0138] The humidity adjusting unit 52 is not particularly limited, but may be a rotor equipped with an adsorption element. The adsorption element may have a moisture adsorption ability that depends on temperature and releases absorbed moisture by heating. In this case, a controllable heater is used together with the adsorption element.
[0139] The above air treatment device 100 may be used as an outdoor air treatment device in which the intake port 50a of the casing 50 is open to the outdoors and the exhaust port 50b of the casing 50 is open to the indoors. EXAMPLES
[0140] The contents of the present disclosure will be specifically described below with reference to examples and comparative examples.
[0141] Example 1 As the antifungal air filter medium of Example 1, an antifungal air filter medium having a configuration as shown in FIG. 3 was prepared.
[0142] Specifically, the upstream breathable support material 21a and the downstream breathable support material 21b are both made of spunbond nonwoven fabric (average fiber diameter 20 μm, basis weight 40 g / m) made of fibers with a core / sheath structure using PET as the core and PE as the sheath. 2 The first porous membrane 31a arranged on the upstream side of the air flow passing through the filter medium and the second porous membrane 31b arranged on the downstream side were obtained by the following process.
[0143] 66.5% by weight (polymer equivalent) of PTFE aqueous dispersion (PTFE-A) with SSG of 2.160, 28.5% by weight (polymer equivalent) of low molecular weight PTFE aqueous dispersion (PTFE-B) with melt viscosity of 20000 Pa·s measured by flow tester method at 380℃, and 5% by weight (polymer equivalent) of FEP aqueous dispersion with melting point of 215℃ were mixed, and 500ml of 1% aluminum nitrate aqueous solution was added as a coagulant, and co-coagulation was performed by stirring. Then, the resulting powder was drained using a sieve, and further dried in a hot air drying oven at 135℃ for 18 hours to obtain a mixed powder of the above three components.
[0144] Next, 36 parts by weight of hydrocarbon oil (Idemitsu Kosan's "IP Solvent 2028") was added as a liquid lubricant (extrusion aid) at 20°C per 100 parts by weight of the mixed powder and mixed. Next, the resulting mixture was extruded using a paste extrusion device to obtain a sheet-shaped molded body. A sheet die with a rectangular extrusion port having a short side length of 2 mm and a long side length of 180 mm was attached to the tip of the paste extrusion device. This sheet-shaped molded body was formed into a film shape by a calendar roll heated to 70°C to obtain a fluororesin film. This film was passed through a hot air drying oven at 200°C to evaporate and remove the hydrocarbon oil, and a strip-shaped unsintered fluororesin film (first raw tape) with an average thickness of 300 μm and an average width of 180 mm was obtained. In addition, a strip-shaped unsintered fluororesin film (second raw tape) with an average thickness of 300 μm and an average width of 180 mm was obtained in the same manner as the first raw tape, except that the amount of the liquid lubricant mixed was 34 parts by weight.
[0145] Next, the first raw tape and the second raw tape were overlapped and stretched in the longitudinal direction (longitudinal direction) at a stretching ratio of 6.5 times. The stretching temperature was 280 ° C. Next, the overlapped and stretched raw tape was stretched in the width direction (transverse direction) at a stretching ratio of 12.0 times using a tenter that can be continuously clipped, and heat-fixed. The stretching temperature at this time was 290 ° C., and the heat-fixing temperature was 390 ° C. As a result, a multi-layer porous membrane in which the first porous membrane and the second porous membrane were overlapped was obtained. Then, the upstream air-permeable support material 21a and the downstream air-permeable support material 21b were bonded by heat fusion to both sides (outer layer side) of the obtained two-layer porous membrane using a laminating device, and a four-layered filter medium shown in FIG. 3 was obtained.
[0146] Example 2 As the antifungal air filter medium of Example 2, an antifungal air filter medium having a configuration as shown in FIG. 3 was prepared.
[0147] Specifically, in Example 2, the upstream gas-permeable support material 21a and the downstream gas-permeable support material 21b were used similarly to those in Example 1. In addition, the first porous membrane 31a arranged on the upstream side of the air flow passing through the filter medium and the second porous membrane 31b arranged on the downstream side were obtained by the following process.
[0148] 66.5% by weight (polymer equivalent) of PTFE aqueous dispersion (PTFE-A) with SSG of 2.160, 28.5% by weight (polymer equivalent) of low molecular weight PTFE aqueous dispersion (PTFE-B) with melt viscosity of 20000 Pa·s measured by flow tester method at 380℃, and 5% by weight (polymer equivalent) of FEP aqueous dispersion with melting point of 215℃ were mixed, and 500ml of 1% aluminum nitrate aqueous solution was added as a coagulant, and co-coagulation was performed by stirring. Then, the resulting powder was drained using a sieve, and further dried in a hot air drying oven at 135℃ for 18 hours to obtain a mixed powder of the above three components.
[0149] Next, 33.5 parts by weight of hydrocarbon oil (Idemitsu Kosan's "IP Solvent 2028") was added as a liquid lubricant (extrusion aid) at 20°C per 100 parts by weight of the mixed powder and mixed. Next, the resulting mixture was extruded using a paste extrusion device to obtain a sheet-shaped molded body. A sheet die with a rectangular extrusion port having a short side length of 2 mm and a long side length of 180 mm was attached to the tip of the paste extrusion device. This sheet-shaped molded body was formed into a film shape by a calendar roll heated to 70°C to obtain a fluororesin film. This film was passed through a hot air drying oven at 200°C to evaporate and remove the hydrocarbon oil, and a strip-shaped unsintered fluororesin film (first raw tape) with an average thickness of 300 μm and an average width of 180 mm was obtained. In addition, a strip-shaped unsintered fluororesin film (second raw tape) with an average thickness of 300 μm and an average width of 180 mm was obtained in the same manner as the first raw tape, except that the amount of the liquid lubricant mixed was 30 parts by weight.
[0150] Next, the first raw tape and the second raw tape were overlapped and stretched in the longitudinal direction (longitudinal direction) at a stretching ratio of 6.5 times. The stretching temperature was 280 ° C. Next, the overlapped and stretched raw tape was stretched in the width direction (transverse direction) at a stretching ratio of 13.7 times using a tenter that can be continuously clipped, and heat-fixed. The stretching temperature at this time was 290 ° C., and the heat-fixing temperature was 390 ° C. As a result, a multi-layer porous membrane in which the first porous membrane and the second porous membrane were overlapped was obtained. Then, the upstream air-permeable support material 21a and the downstream air-permeable support material 21b were bonded by heat fusion to both sides (outer layer side) of the obtained two-layer porous membrane using a laminating device, and a four-layered filter medium shown in FIG. 3 was obtained.
[0151] Example 3 As the antifungal air filter medium of Example 3, an antifungal air filter medium having a configuration as shown in FIG. 3 was prepared.
[0152] In Example 3, the upstream air permeability support material 21a and the downstream air permeability support material 21b were used similarly to those in Example 1. In addition, the first porous membrane 31a arranged on the upstream side of the air flow passing through the filter medium and the second porous membrane 31b arranged on the downstream side were obtained by the following process.
[0153] As the raw material of embodiment 3, use the mixed powder that is obtained by co-coagulation mixing of the fine powder of perfluoroalkyl vinyl ether modified polytetrafluoroethylene, which is the copolymer of tetrafluoroethylene and perfluoroalkyl vinyl ether, and the fine powder of polytetrafluoroethylene with average molecular weight of 6.5 million (manufactured by Daikin Industries, Ltd., product name: F106) with weight ratio of 75:25.
[0154] The mixed powder was mixed with an extrusion aid (liquid lubricant) in an amount of 29% by weight, and a sheet die with a rectangular extrusion opening measuring 2 mm in the short direction and 170 mm in the long direction was attached. Using the method of Example 1, a strip-shaped unsintered fluororesin film (first raw tape) with an average thickness of 300 μm and an average width of 170 mm was obtained.
[0155] In addition, an extrusion aid (liquid lubricant) was mixed in an amount of 24% by weight of the above mixed powder, and a strip-shaped unsintered fluororesin film (second raw tape) having an average thickness of 300 μm and an average width of 170 mm was obtained by the method of Example 1.
[0156] The first raw tape and the second raw tape were overlapped and stretched in the longitudinal direction (longitudinal direction) at a stretching ratio of 8 times. The stretching temperature was 250 ° C. Next, the overlapped and stretched raw tape was stretched in the width direction (transverse direction) at a stretching ratio of 20.0 times using a tenter that can be continuously clipped, and heat-fixed. The stretching temperature at this time was 290 ° C., and the heat-fixing temperature was 390 ° C. As a result, a multi-layer porous membrane in which the first porous membrane and the second porous membrane were overlapped was obtained. Then, the upstream air-permeable support material 21a and the downstream air-permeable support material 21b were bonded by heat fusion to both sides (outer layer side) of the obtained two-layer porous membrane using a laminating device, and a four-layered filter medium shown in FIG. 3 was obtained.
[0157] Example 4 As the antifungal air filter medium of Example 4, an antifungal air filter medium having a configuration as shown in FIG. 3 was prepared.
[0158] In Example 4, the upstream gas permeable support material 21a and the downstream gas permeable support material 21b were used similarly to those in Example 1. In addition, the first porous membrane 31a arranged on the upstream side of the air flow passing through the filter medium and the second porous membrane 31b arranged on the downstream side were obtained by the following process.
[0159] As the raw material of embodiment 2, use the mixed powder of perfluoroalkylvinylether modified polytetrafluoroethylene fine powder, which is the copolymer of tetrafluoroethylene and perfluoroalkylvinylether, and the fine powder of polytetrafluoroethylene with average molecular weight of 6.5 million (manufactured by Daikin Industries, Ltd., product name: F106) by weight ratio of 75:25.
[0160] An extrusion aid (liquid lubricant) was added in an amount of 28% by weight of the mixed powder, and a strip-shaped unsintered fluororesin film (first raw tape) with an average thickness of 300 μm and an average width of 180 mm was obtained using the method of Example 1.
[0161] In addition, an extrusion aid (liquid lubricant) was mixed in an amount of 24% by weight of the above mixed powder, and a strip-shaped unsintered fluororesin film (second raw tape) having an average thickness of 300 μm and an average width of 180 mm was obtained by the method of Example 1.
[0162] The first raw tape and the second raw tape were overlapped and stretched in the longitudinal direction (longitudinal direction) at a stretching ratio of 8 times. The stretching temperature was 280 ° C. Next, the overlapped and stretched raw tape was stretched in the width direction (transverse direction) at a stretching ratio of 22.0 times using a tenter that can be continuously clipped, and heat-fixed. The stretching temperature at this time was 290 ° C., and the heat-fixing temperature was 390 ° C. As a result, a multi-layer porous membrane in which the first porous membrane and the second porous membrane were overlapped was obtained. Then, the upstream breathable support material 21a and the downstream breathable support material 21b were bonded by heat fusion to both sides (outer layer side) of the obtained two-layer porous membrane using a laminating device, and a four-layered filter medium shown in FIG. 3 was obtained.
[0163] Example 5 As the antifungal air filter medium of Example 5, an antifungal air filter medium having a configuration as shown in FIG. 2 was prepared.
[0164] In Example 5, the upstream-permeable support material 21a and the downstream-permeable support material 21b were the same as those in Example 1.
[0165] The porous membrane 31 used was obtained by the following process.
[0166] As the raw material of Example 5, a fine powder of polytetrafluoroethylene having an average molecular weight of 6.5 million (manufactured by Daikin Industries, Ltd., product name: F106) was used. 33 parts by weight of liquid lubricant was added and mixed per 100 parts by weight of PTFE fine powder, and the mixture obtained was extruded using a paste extrusion device to obtain a round bar-shaped molded body. This round bar-shaped molded body was formed into a film shape by a calendar roll heated to 70 ° C. to obtain a PTFE film. This film was passed through a hot air drying oven at 200 ° C. to evaporate and remove the hydrocarbon oil, and a strip-shaped unsintered PTFE film with an average thickness of 200 μm and an average width of 150 mm was obtained. This unsintered PTFE film was stretched in the longitudinal direction at a stretch ratio of 6.5 times. The stretching temperature was 280 ° C. Next, the stretched unsintered PTFE film was stretched in the width direction at a stretch ratio of 32.0 times using a tenter that can be continuously clipped, and heat set. The stretching temperature at this time was 290 ° C., and the heat setting temperature was 390 ° C. The upstream-permeable support material 21a and the downstream-permeable support material 21b were bonded to both sides (outer layer sides) of the porous membrane obtained by this by heat fusion using a laminating device, to obtain a filter medium with a three-layer structure as shown in FIG.
[0167] Example 6 As the antifungal air filter medium of Example 6, an antifungal air filter medium having a configuration as shown in FIG. 2 was prepared.
[0168] Specifically, the upstream breathable support material 21a, the intermediate breathable support material 21c, and the downstream breathable support material 21b are all made of spunbond nonwoven fabric (average fiber diameter 20 μm, basis weight 30 g / m) made of fibers with a core / sheath structure using PET as the core and PE as the sheath.2 , thickness 0.2 mm) was used.
[0169] The porous membrane 31 used was obtained by the following process.
[0170] As a raw material, 100 parts by weight of the mixed powder of the same three components as in Example 1 was mixed with 34 parts by weight of a hydrocarbon oil (Idemitsu Kosan's "IP Solvent 2028") as a liquid lubricant (extrusion aid) at 20°C. The mixture obtained was extruded using a paste extrusion device to obtain a sheet-shaped molded body. A sheet die with a rectangular extrusion port having a short side length of 2 mm and a long side length of 220 mm was attached to the tip of the paste extrusion device. This sheet-shaped molded body was formed into a film by a calendar roll heated to 70°C to obtain a fluororesin film. This film was passed through a hot air drying oven at 200°C to evaporate and remove the hydrocarbon oil, and a strip-shaped unsintered fluororesin film with an average thickness of 300 μm and an average width of 220 mm was obtained.
[0171] This unsintered PTFE film was stretched in the longitudinal direction (longitudinal direction) at a stretching ratio of 6.5 times. The stretching temperature was 280 ° C. Next, the stretched unsintered PTFE film was stretched in the width direction (lateral direction) at a stretching ratio of 11.0 times using a tenter that can be continuously clipped, and heat-fixed. The stretching temperature at this time was 290 ° C., and the heat-fixing temperature was 390 ° C. The upstream gas-permeable support material 21a and the downstream gas-permeable support material 21b were bonded to both sides (outer layer sides) of the porous membrane obtained by this by using a laminating device by heat fusion, and a three-layered filter medium shown in FIG. 2 was obtained.
[0172] Comparative Example 1 As the air filter medium of Comparative Example 1, a commonly available PTFE air filter medium having a configuration as shown in FIG. 2 was prepared.
[0173] The physical properties measured in the examples and comparative examples are as follows.
[0174] (Thickness of porous membrane) Using a thickness gauge (1D-110MH, manufactured by Mitutoyo Corporation), five measurement targets were stacked and the total thickness was measured, and the value was divided by 5 to obtain the thickness of one sheet.
[0175] In the examples in which two porous membranes were used, the total thickness was regarded as the membrane thickness.
[0176] (Average pore size of porous membrane) The mean flow pore size measured according to the description of ASTM F316-86 was taken as the mean pore size (mean flow path size) of the porous membrane. The actual measurement was performed using a PMI Capillary Flow Prometer CFP-1100A (manufactured by PIM).
[0177] In addition, in the case where a plurality of porous membranes were present, the average pore size was measured for the plurality of overlapping porous membranes.
[0178] (Average surface height of porous membrane Rc) The average height Rc of the surface of the porous membrane was measured using a laser microscope VK-9710 (manufactured by Keyence Corporation) in accordance with the method described in JIS B 0601:2013 (ISO 4287:1997, Amd.1:2009). The measurement conditions were: microscope magnification: 20 times (monitor: 400 times), measurement area: 130 μm, roughness standard: ISO 4287 (JIS B0601:2013). The average height Rc of the surface of the porous membrane was obtained from the obtained image using image analysis software (VK Analyzer). Note that, under the above conditions, three points were measured while changing the measurement points on the surface of the porous membrane, and the average height Rc was calculated as the average value.
[0179] In addition, in the case where a plurality of porous membranes were present, the measurement was performed on the surface of the porous membrane located on the upstream side of the passing air current.
[0180] (Arithmetic mean roughness Ra of porous membrane surface) The arithmetic mean roughness Ra of the surface of the porous membrane was measured using a laser microscope VK-9710 (manufactured by Keyence Corporation) in accordance with the method described in JIS B 0601 (2013). The measurement conditions were: microscope magnification: 20 times (monitor: 400 times), magnification: 20 times, measurement area: 130 μm, roughness standard: ISO 4287 (JIS B 0601: 2013). Using image analysis software (VK Analyzer), the arithmetic mean roughness Ra of the surface of the porous membrane was obtained from the obtained image. Note that, under the above conditions, three points were measured while changing the measurement points on the surface of the porous membrane, and the arithmetic mean roughness Ra was calculated as the average value.
[0181] In addition, in the case where a plurality of porous membranes were present, the measurement was performed on the surface of the porous membrane located on the upstream side of the passing air current.
[0182] (Water contact angle on the surface of the porous membrane) The contact angle was determined by the 2 / θ method using a Drop Master 501 (Kyowa Interface Science Co., Ltd.).
[0183] (Contact angle of the porous membrane surface with water:IPA=80:20) The contact angle was determined by the 2 / θ method using a Drop Master 501 (Kyowa Interface Science Co., Ltd.).
[0184] (Contact angle of the porous membrane surface with water:IPA=70:30) The contact angle was determined by the 2 / θ method using a Drop Master 501 (Kyowa Interface Science Co., Ltd.).
[0185] In addition, in the case where a plurality of porous membranes were present, the above-mentioned contact angles were measured on the surface of the porous membrane located on the upstream side of the passing air flow.
[0186] (Weight of porous membrane) The basis weight was determined by dividing the mass (g) of a sample cut into a rectangle of a given area by the area measured with a precision balance. For examples using two porous membranes, the basis weight was determined for a sample in which multiple porous membranes were overlapped.
[0187] (Pressure loss) A measurement sample of the antifungal air filter medium was set in a filter holder with a diameter of 100 mm, the inlet side was pressurized with a compressor, and the air flow rate was adjusted to 5.3 cm / sec with a flow meter. The pressure loss at this time was measured with a manometer.
[0188] (Collection efficiency of NaCl particles with a particle diameter of 0.1 μm) According to the method described in JIS B9928 Appendix 5 (Regulations) NaCl aerosol generation method (pressure spray method), NaCl particles generated by an atomizer were classified to a particle size of 0.1 μm using an electrostatic classifier (TSI), and the particle charge was neutralized using americium-241. The permeation flow rate was then adjusted to 5.3 cm / sec. A particle counter (TSI, CNC) was used to determine the number of particles before and after the antifungal air filter medium, which was the measurement sample, and the collection efficiency was calculated using the following formula. Transmittance (%)=(CO / CI)×100 Collection efficiency (%) = 100 - transmittance (%) CO = Number of 0.1 μm NaCl particles downstream of the measurement sample CI = Number of NaCl 0.1 μm particles upstream of the measurement sample (JIS Z2911 mold resistance test (wet method))
[0189] The above-mentioned Examples 1, 5, and Comparative Example 1 were subjected to a test for mold resistance in accordance with JIS Z2911.
[0190] The samples were cut to a specified size and placed on an agar medium containing ammonium nitrate, potassium dihydrogen phosphate, magnesium sulfate heptahydrate, potassium chloride, ferrous sulfate (II) heptahydrate, agar, and purified water. A mixed spore liquid containing spores of Aspergillus niger, Penicillium citrinum, Chaetomium globosum, and Myrothecium verrucaria was sprayed onto the samples, and the condition of mold growth on the sample surface was observed at a temperature of 26±2°C.
[0191] Here, in assessing the mold growth status in the mold resistance test, samples in which no hyphae growth was observed with the naked eye were rated 0, samples in which the area in which hyphae growth was observed did not exceed 1 / 3 of the total area were rated 1, and samples in which the area in which hyphae growth was observed exceeded 1 / 3 of the total area were rated 2.
[0192] (Test conforming to JIS Z2911 mold resistance test) For each of the above examples and comparative examples, a test conforming to the mold resistance test of JIS Z2911 was conducted by cutting samples to a specified size, placing them on potato dextrose agar medium, sprinkling a suspension of Aspergillus niger (1000 RLU), and leaving them at room temperature. The degree of mold growth on the sample surface was observed with the naked eye over time (after 3 days, 1 week, and 2 weeks).
[0193] (ISO 846 Plastics - Evaluation of microbial activity) For Example 1 and Example 3, tests were conducted using ISO 846:2019 (Method A) to examine the resistance of the specimens to mold. In the test, the test mold was inoculated onto a malt extract agar medium and cultured at 29±1°C for 10 to 20 days, and then the number of spores was reduced to 10 using an inorganic salt solution. 6 The spore solution was prepared so that the concentration was 1 / mL, and the mixture was used as the test spore solution. The test molds used were Aspergillus niger (NBRC 105649), Penicillium pinophilum (NBRC 100533), Paecilomyces variotii (NBRC 107725), Trichoderma virens (NBRC 6355), and Chaetomium globosum (NBRC 6347). The test sample was inoculated with the test spore solution by spraying, and then cultured for 4 weeks under conditions of 29±1°C and a relative humidity of 95% or more. After the second and fourth weeks of culture, the growth of mold on the test sample was observed with the naked eye and by microscope.
[0194] The results corresponding to mycelial growth were as follows: no mold growth observed under a microscope was rated as "0", no mold growth observed with the naked eye but mold observed under a microscope was rated as "1a", no mold growth observed with the naked eye but mold observed under a microscope was rated as "1b", no mold growth observed with the naked eye but mold observed under a microscope was rated as "50% or less of the total sample area", no mold growth observed with the naked eye but mold observed under a microscope was rated as "1c", mycelial growth observed with the naked eye was rated as "2" less than 25% of the total sample area, mycelial growth observed with the naked eye was rated as "3", mycelial growth observed with the naked eye was rated as "4" or more of the total sample area, and mycelial growth was so intense that it covered the entire sample area was rated as "5".
[0195] The physical properties of the antifungal air filter media and the physical properties of the porous membranes of each of the Examples and Comparative Examples are shown in Table 1 below.
[0196] 8 and 9 show photographs of the samples taken 3 days and 1 week after the start of the test in accordance with the JIS Z2911 mold resistance test for Example 1 and Comparative Example 1. Note that the blackened areas in the photographs indicate areas where identification letters were written on the samples and petri dishes, and no mold was found in the blackened areas.
[0197] [Table 1]
[0198] The above contact angle (water) was measured according to the sessile drop method, but since the water did not move, the value shown was measured with the needle still attached.
[0199] Moreover, in the JIS Z2911 mold resistance test, Examples 1 and 5 achieved a score of 0 (no growth of mycelia was observed in the inoculated portion of the sample or test piece), while Comparative Example 1 achieved a score of 1 (the area in which growth of mycelia was observed did not exceed 1 / 3 of the total area).
[0200] In the ISO846 plastic-microbial activity evaluation, Examples 1 and 3 achieved a score of 0 (no mold growth observed under a microscope) both after 2 and 4 weeks of culture. Figure 10 shows photographs of the samples of Examples 1 and 3 after 4 weeks of culture.
[0201] (Additional Note) Although the embodiments of the present disclosure have been described above, it will be understood that various changes in form and details can be made without departing from the spirit and scope of the present disclosure described in the claims. [Explanation of symbols]
[0202] 1 Air filter unit 20 Filter Pack 25 Frame 30a, 30b, 30c, 30d Anti-mold air filter media (air filter media) 21 Breathable support material 21a Upstream breathable support material 21b Downstream breathable support material 21c Intermediate breathable support material 31 Porous Membrane 31a First porous membrane 31b Second porous membrane 50 Casing 50a Intake port 50b Air outlet 51 Heat exchanger 52 Humidity adjustment section 53 Fans 100 Outdoor air treatment device [Prior art documents] [Patent documents]
[0203] [Patent Document 1] JP 2003-205211 A
Claims
1. A porous membrane having an average surface height Rc of 6 μm or more and a water contact angle of the membrane surface of 90 degrees or more. Air filter media.
2. The average height Rc of the surface of the porous membrane is 36 μm or more. The air filter medium according to claim 1 .
3. The arithmetic average roughness Ra of the surface of the porous membrane is 6 μm or more; The air filter medium according to claim 1 or 2.
4. The average pore size of the porous membrane is 2 μm or more. The air filter medium according to claim 1 or 2.
5. The average pore size of the porous membrane is 10 μm or less. The air filter medium according to claim 1 or 2.
6. The thickness of the porous membrane is 100 μm or more. The air filter medium according to claim 1 or 2.
7. The contact angle of a 30% by volume aqueous solution of isopropyl alcohol is 127 degrees or more. The air filter medium according to claim 1 or 2.
8. The porous membrane contains a fluororesin. The air filter medium according to claim 1 or 2.
9. The porous membrane does not contain a mold inhibitor. The air filter medium according to claim 1 or 2.
10. Used in an environment with a relative humidity of 60% or more. The air filter medium according to claim 1 or 2.
11. A method for using the antifungal air filter medium according to claim 1 or 2 in an environment with a relative humidity of 60% or more.
12. The air filter medium according to claim 1 or 2 is provided. Air treatment equipment.
Citation Information
Patent Citations
Recording paper cut-off mechanism of facsimile equipment
JP1986095662A
Fluorinated porous polyolefin film
JP1995053763A
Porous film
JP2016019970A
Porous film
JP2016019972A
Air filter medium, air filter pack, and air filter unit
JP2018051544A